2014
DOI: 10.1111/apa.12757
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity has a negative but weak association with academic performance in children and adolescents

Abstract: Objectively measured physical activity may influence academic performance during both childhood and adolescence, but this association was negative and very weak. Longitudinal and intervention studies are necessary to further our understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 26 publications
4
46
0
3
Order By: Relevance
“…Regarding MVPA, 2/3 studies reported at least 1 unfavourable association (Esteban-Cornejo et al 2014;Young et al 2014) and 1/3 studies reported at least 1 favourable association (Booth et al 2013) with academic achievement. One study examined MPA and reported unfavourable associations with school grades across subjects and with GPA (Esteban-Cornejo et al 2014). Where associations were not uniform, findings varied by school subject, sex, and/or sample.…”
Section: Cognition/academic Achievementmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding MVPA, 2/3 studies reported at least 1 unfavourable association (Esteban-Cornejo et al 2014;Young et al 2014) and 1/3 studies reported at least 1 favourable association (Booth et al 2013) with academic achievement. One study examined MPA and reported unfavourable associations with school grades across subjects and with GPA (Esteban-Cornejo et al 2014). Where associations were not uniform, findings varied by school subject, sex, and/or sample.…”
Section: Cognition/academic Achievementmentioning
confidence: 99%
“…i Includes 6 cross-sectional studies (Booth et al 2013(Booth et al , 2014Lambourne et al 2013;Esteban-Cornejo et al 2014;Hansen et al 2014;Young et al 2014) from 5 unique samples. Two studies reported data from the ALSPAC sample (Booth et al 2013(Booth et al , 2014; results are reported separately and participants are only counted once.…”
Section: Physical Fitnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies which investigated the association between PAL and academic performance have found a positive relationship between academic performance and PAL, especially regarding vigorous activities 18,19 however, others have not found this association 20,21 . Morales et al 22 found a linear relation between self-reported daily PAL and academic performance.…”
Section: Discussionmentioning
confidence: 99%